Poor sleep quality and associated factors among healthcare professionals at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Tesfaye, Winta; Getu, Ayechew Adera; Dagnew, Baye; Lemma, Alemu; Yeshaw, Yigizie (Frontiers in Psychiatry, 2024)
Background: Poor sleep quality is linked to physiological dysfunction, which increases the risk of obesity, cardiovascular disease, cognitive impairment, and other medical conditions. Despite the known health risk of sleep disturbances, literature is still scant regarding sleep quality and its associated factors among health care professionals in Ethiopia.Therefore, this study aimed to determine the prevalence of poor sleep quality and its associated factors among health care professionals at the University of Gondar Comprehensive Specialized Hospital.Comprehensive Specialized Hospital, Northwest Ethiopia. A total of 418 health care professionals participated in the study. The study participants were chosen using the stratified random sampling method. Data were collected using a structured, self-administered questionnaire. The Pittsburgh Sleep Quality Index (PSQI) was used to assess the sleep quality of participants. Bi-variable and multi-variable logistic regression were used. P ≤ 0.05 was used to declare statistically significant variables.The mean age of the study participants was 30.7 years (SD ± 6.3). The overall prevalence of poor sleep quality was 58.9% [95% CI (54.2, 63.6%)]. Being female [AOR=1.9, 95%CI (1.2, 2.9)], shift worker [AOR=5.7, 95%CI (2.3, 14.3), not performing regular exercise [AOR=2.08(1.2-3.6)], khat chewer [AOR = 3.1, 95% CI (1.2, 7.6)] and having depressive symptoms [AOR = 2.6, 95% CI (1.3, 6.8)] were significantly associated with higher odds of having poor sleep quality.the prevalence of poor sleep quality among health care professionals was found to be high. As a result, we recommend that health care providers at the University of Gondar comprehensive and specialized hospital focus on early regular screening for sleep disturbances, as well as pay special attention to shift work schedules and behaviors such as khat chewing, exercise, and depressive symptoms.